Contesting transdisciplinary climate knowledge: a decolonial perspective on the FRACTAL project in Windhoek, Namibia - Pelaez, Avila Julia Peláez (Department of Environmental and Geographical Science, 2020)
Recent trends in sustainability research have particularly propagated transdisciplinary approaches in knowledge production. These new modes of knowledge production seek to deconstruct universalist principles and epistemic authorities from positivist research approaches. The potential of replicating existing power dynamics into these transdisciplinary spaces has, however, not sufficiently been critically questioned yet. This study proposes that transformative change in development of African cities requires a deconstruction of these power dynamics, that current transdisciplinary sustainability research is not yet sufficiently engaging in. To examine the power dynamics, the study applied a decolonial lens in its analysis. In a novel approach to contesting climate knowledge, the study sought to deconstruct the foundational concepts that are operationalised in the transdisciplinary knowledge generation. The analysis focused on tracing assumptions to identify imaginaries, that construct the geopolitical space and condition knowledge politics within a transdisciplinary research programme in Windhoek, Namibia. It further sought to reveal the mechanisms in the programmatic research design that condition epistemic authorities and subjectivities in the collaborative processes. Power dynamics were traceable through imaginaries as well as the evidencing of epistemic authority. Two overarching imaginaries could be traced, which are based in the construction and engagement of the geopolitical space in Windhoek: the imaginary of the social impact and desirable future and the imaginary of the sciencepolicy interface. Both imaginaries were underpinned by the vision of transformation, whose operationalisation revealed to be instrumental in determining the actual transformational potential in contrast to the envisioned one. The analysis indicated the concept of transformation to be an inhibiting factor due to uncontested power dynamics that were replicated in the transdisciplinary space. Epistemic authority was especially evident in connection with the climate information that was generated to inform the knowledge co-production. A contestation of authoritative knowledge was evident with regards to contextualising the information for present and future climates in Windhoek. However, the scientific climate information itself was not questioned for its authority. The conceptual design of the stakeholder engagement revealed to be the main mechanism that created subjectivity. The study concluded with an exploratory section, an ‘epistemic disobedience’, which engages the principle of Walking With that is used by the indigenous activist movement of the Zapatistas in Mexico to create a vision of a new world. Walking With is used to reconstruct a vision of a decolonial approach to generating climate knowledge in an African urban space. This exploration further exemplifies a dimension of decolonial criticism, which is the importance of going beyond deconstruction towards fostering decolonial thinking.